Power Dynamics in African Forests The Politics of Global Sustainability - Ongolo, Symphorien; Krott, Max (Routledge Studies in African Politics and International Relations, 2024)
This book addresses historical perspectives and contemporary challenges of the politics of forestland governance and the related sustainability crisis in Africa. It focusses on the power dynamics between key actors involved in the governance of forest-related resources either for their exploitation or with regards to biodiversity conservation policies promoted at international arenas. The book provides conceptual and empirical contributions on what happens when global sustainability agendas and the related policy instruments meet the realities of domestic politics in Africa. It reveals that several actors in forest-rich countries, especially those with limited sovereignty, have often employed complex informal strategies as the 'weapon of the weak' to resist the domination of the most powerful actors of global environmental politics.